Rare‐Earth Metal Tetrathiafulvalene Carboxylate Frameworks as Redox‐Switchable Single‐Molecule Magnets. Issue 2 (3rd December 2020) - Su, Jian; Yuan, Shuai; Li, Jing; Wang, Hai‐Ying; Ge, Jing‐Yuan; Drake, Hannah F.; Leong, Chanel F.; Yu, Fei; D'Alessandro, Deanna M.; Kurmoo, Mohamedally; Zuo, Jing‐Lin; Zhou, Hong‐Cai
Abstract: Using the redox‐active tetrathiafulvalene tetrabenzoate (TTFTB 4− ) as the linker, a series of stable and porous rare‐earth metal–organic frameworks (RE‐MOFs), [RE9 (μ3 ‐OH)13 (μ3 ‐O)(H2 O)9 (TTFTB)3 ] (1‐RE, where RE=Y, Sm, Gd, Tb, Dy, Ho, and Er) were constructed. The RE9 (μ3 ‐OH)13 (μ3 ‐O) (H2 O)9 ](CO2 )12 clusters within 1‐RE act as segregated single‐molecule magnets (SMMs) displaying slow relaxation. Interestingly, upon oxidation by I2, the S= 0 TTFTB 4− linkers of 1‐RE were converted into S = 1 / 2 TTFTB .3− radical linkers which introduced exchange‐coupling between SMMs and modulated the relaxation. Furthermore, the SMM property can be restored by reduction in N, N ‐dimethylformamide. These results highlight the advantage of MOFs in the construction of redox‐switchable SMMs. Abstract : Redox switchable single‐molecule magnets (SMM) arranged in ordered architectures are valuable objects for use in memory devices. A metal–organic framework is an ideal platform to integrate SMM as nodes and redox‐active organic linkers as switching probes (see figure).